POLA PERURATAN DAUN KELOPAK, DAUN MAHKOTA, DAN DAUN PADA SUKU APOCYNACEAE - Eko Sri Sulasmi; Siti Rachmawati (PTTI, 2013)
The pattern leaf venation of Apocynaceae is brochidodromous, intercosta pa-tterns are reticulate and parallel with anastomose ending and blind. There is no report of venation pattern of sepal and petal. Perianthium is derivated from leaf as the result of tropofil differentiation, while pistil and stamen are derivated from sporofil. This research aims to interpret the character of sepal and petalas modification of leaf refer to leaf venation pattern in Apocynaceae. Leaf clearing method was used in this research. The result showed that within 8 genera of Apocynaceae, the venation pattern of sepal and petal is more simple than leaf in primary vein, branch of primary vein, secondary vein, areolar, and vein endings. Sepal and petal have not secondary vein and doesn’t made intercosta and areolar region. Leaf has intercosta and areolar region. Pattern of vein ending in sepal and petal is blind ending, and leaf vein ending pattern anastomose, blind ending, and branched two or three times. Sepal and petal are modification of leaf that has more primary vein.It does not form vein, intercosta region, and blind ending.